Nutritional security through horticulture - Janakiram, T; Das, Manish (Indian Horticulture, 2018)
Horticultural crops are main components of a healthy diet. The constituents obtained by human body from fruits and vegetables include water, carbohydrates, fats, proteins, fibres, minerals, organic acids, pigments, vitamins and antioxidants, among others. Fruits and vegetables, are a good source of fibres, selected minerals, vitamins and antioxidants. Most fruits and vegetables are available almost year-round in a wide variety and they not only taste good, but they also have favourable attributes of texture, colour, flavour anÂ ease of use. They can be fresh, cooked, hot or cold, canned, pickled, frozen or dried. The existing growth of horticultural crops is economically rewarding. This sector is expected to grow and contribute to food and nutritional security, provided, the sector is nurtured with focused infrastructural development and has a conducive policy environment. The answer in horticulture, therefore lies in vertical growth in terms of appropriate location-specific high-value crops with maximum productivity and cost effectiveness. After attaining food security, emphasis on production, protection and post-harvest management of horticultural crops needs to be laid to achieve nutritional security.